Training on Environmentally Friendly Appropriate Science and Technology Based Household Waste Management : Pelatihan Pengelolaan Limbah Rumah Tangga Berbasis Iptek Tepat Guna yang Ramah Lingkungan - Azis, Rahmawati; Juhanto, Asrijun; Amiruddin, Fitriyah; Sambu’, Esrianti; Samsidarwati, Besse; Utami, Nurul Salsabila; Akmal, Akmal (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
Household waste management in Simbang Village has not been carried out optimally, where the administration has not maximized the 3R system (reduce, reuse, and recycle), low knowledge, positive attitudes, and skills in waste utilization and management, have not been utilized for economic improvement and empowerment. Implement methods to overcome partner problems: Planning, Action (Health promotion, counseling, Procurement and utilization of technology to produce waste recycling products, Training and simulation, Coaching and mentoring), Observation and Evaluation, and Reflection. The results of the training showed an increase in knowledge (81%), positive attitudes (76.2%), and skills (100%) in processing organic waste into solid and leachate compost (liquid compost), as well as positive behaviors related to waste management by starting to implement new behaviors in the form of "prevent, sort, and reuse". Through training based on environmentally friendly science and technology, the community and village government can be more aware and skilled in managing household waste to contribute to environmental sustainability positively.